Algeria’s National Reconciliation: An Analytical Approach - Bouandel , Youcef; Al Zandani , Bakeel (المجلة الجزائرية للأمن الإنساني, 2019)
After the removal of a dictatorial regime or a period of civil unrest, national reconciliation strategies, including amnesties, have been used as tools for dealing with past atrocities and paving the way for a process of a transition. Algeria’s measures which include, the Rahma law, the Law on Civil Harmony and the Charter for National Reconciliation have not only been one sided, but did not go far enough in dealing with the conflict. They have managed to drastically reduce the level of violence and achieved peace in the short-run, but it is doubtful that long and lasting peace would be achieved unless the Algerian authorities would take further steps and build on what has been achieved thus far.